Diagnoza społeczności lokalnej dla celów animacji i aktywizacji - Smykowski, Błażej; Rosińska, Agnieszka (Człowiek i Społeczeństwo, 2015)
Błażej Smykowski, Agnieszka Rosińska, Diagnoza społeczności lokalnej dla celów animacji i aktywizacji [Diagnosing a local community for the purposes of social animation and community organizing], edited by Z. Drozdowicz, S. Sztajer, „Człowiek i Społeczeństwo”, vol. XXXIX, Poznań 2015, pp. 197-214, Adam Mickiewicz University Press. ISBN 978-83-232-2953-7, ISSN 0239-3271. The paper discusses the problem of diagnosing a local community for the purposes of social animation and community organizing activities. Its main goal is to create a general theoretical framework for the development of specific procedures and tools that could be harnessed in such a diagnosis. For such a framework to be created it is necessary to clarify basic terms and concepts. The focus of this paper is on the concepts of social animation and community organizing. The differentiation between the two makes it possible to develop two different diagnostic procedures. Drawing on the social theory and practice we have attempted to describe and explain these two concepts. The relations between social animation and community organizing constitute the key conclusions of our paper. In the process of diagnosing a social system it is vital to decide whether the goal is to strengthen the system through inspiring and promoting social activity or through developing new structures within and around the system. This paper concludes by stressing the role and significance of a professional diagnosis whenever an intervention in a community is planned and when the aim is to understand its development process.